Antecedents and Consequences of Personal Selling, Price and Product Quality on Buying Incentive Packages Tour Travel Post- Covid-19 Pandemic - Catur Widayati, C.; ., Yenita; Arijanto, Agus; Ayu Diporini, Vidya; Edwina Oebit, Cut; Suryaningrum, Dwi (KnE Social Sciences, 2023)
The development of the world of tourism, which continues to increase is certainly a support for the Tour and Travel business. One of the attractions of a tourist is a tourist attraction. Therefore, tourists need in their tour to travel to places that are interesting and able to provide comfort, serenity, and joy in itself. The purpose of this study to find out the relationship of personal sales service, price perception, and quality product to the package purchase of the travel package incentives. The object of this study is all customers of Preferred Tours Management Jakarta. The sample in this study are Preferred Tours Management customers in Jakarta, with 155 respondents. Purposive sampling method was used and the sample were selected based on its characteristics. Data were processed using Smart PLS (partial least square) 3.0. The results of hypothesis testing in this research explain that service quality influences purchasing decisions, but price has a negative and significant effect. Besides, product quality also has a significant influence. Therefore, considering the existing market, the company requests an increase in purchases by paying attention to service quality and product quality through the application of attractive prices. Keywords: service quality, price, product quality, purchasing decisions